Collaboration, Agility, and Redundancy: Key Strategies for Managing Global Supply Chain Disruptions - Uvi Dwian Kencono; Yakuttinah Marjan; Dimas Endrawan Putra; Ahnis Zulkarnain (Logistica : Journal of Logistic and Transportation, 2025)
Global supply chains have become highly vulnerable to disruptions caused by pandemics, geopolitical conflicts, trade wars, and sustainability pressures. This narrative review synthesizes existing research on risk management strategies with a focus on resilience, collaboration, sustainability, and strategic intelligence. Literature searches were conducted in Scopus, Web of Science, and Google Scholar, covering studies published between 2010 and 2024. The findings highlight resilience strategies—such as redundancy, agility, and digitalization—as essential mechanisms for mitigating disruptions. Redundancy reduces operational vulnerabilities through buffer inventories and multiple sourcing, while agility enables rapid adjustments to volatile conditions. Digitalization further enhances resilience by improving real-time monitoring and decision-making. Collaborative governance and risk-sharing contracts strengthen supply chain networks by fostering trust and distributing risks equitably. Geopolitical events and the COVID-19 pandemic illustrate the fragility of global networks, emphasizing the importance of supplier diversification, localization, and technological preparedness. Sustainability-related risks, including environmental, social, and governance (ESG) issues, require integrated frameworks that align resilience strategies with ethical and regulatory imperatives. Strategic intelligence emerges as a dynamic capability that supports proactive adaptation and recovery. This review concludes that effective supply chain risk management requires integrated and adaptive frameworks combining resilience, collaboration, and intelligence. Policy support, investment in logistics infrastructure, and targeted strategies for small and medium-sized enterprises (SMEs) are critical for building sustainable and competitive global supply chains in an increasingly uncertain environment,